Anticipating and responding to pavement performance as climate changes - Dawson, Andrew (Springer, 2014)
As climate changes, the performance of pavements can be expected to change too. More rainfall can be expected to lead to softer subgrades and less sup-port to the pavement structure with consequences for more rapid cracking and rut-ting. Even if the amount of rainfall doesn’t change, many places can expect the rain to fall in less frequent but more intense storms leading to challenges for cur-rent pavement drainage systems. If temperature rises, then asphaltic pavements may be expected to suffer from greater rutting in hot weather; but if the tempera-ture rise causes greater evaporation then improved support conditions could arise; and if the temperature rise is in winter in an area that historically experiences fully frozen conditions in the winter, then weak, thawing pavements could result. Pre-dicting these and other effects of climate change involves an understanding of the sensitivity to climatic effects of both material properties and of overall pavement performance. In turn the predictions of such changes might indicate the need for adaptation in design, construction or materials selection – the extent of the need being dependent on the severity and risk associated with the predicted changes. In this way appropriate responses can be made to the challenges that future climate change will bring. In some places no change to practice may be required. Howev-er, for most authorities the immediate response should be to restate design codes and specifications with climate change in view. Mostly, the practices, techniques and tools for an adequate response are already available but users may need to employ adjusted practice if they don’t want future maintenance demands to be-come excessive.